Modernidade e Política: O DEBATE ENTRE A DEMOCRACIA DELIBERATIVA DE RAWLS E HABERMAS E A DEMOCRACIA AGONÍSTICA DE CHANTAL MOUFFE - Leão, Richard Douglas Coelho; Nascimento Furtado, Arjunuyra (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2021)
This text presents a debate established in modernity in the field of politics, more precisely between the model of deliberative democracy by John Ralws and Jürgen Habermas and the model of agonistic democracy by Chantal Mouffe. The text presents the internal debate established in the deliberative liberal democracy between Ralws and Habermas, mainly around the concepts of Theory of Justice of the former and Communicative Action of the latter. Mouffe makes a deep critical analysis of the assumptions of deliberative democracy, presenting his model of agonistic democracy, which points to the democratic construction made through dissent and debate between the different needs and specificities with a view to providing a fully participatory democracy, to the detriment of the consensus proposed by the supporters of deliberative democracy. The methodology used involves a bibliographic survey of the works that address the topic under discussion, in addition to a critical analysis of concepts such as modernity, democracy and the public use of reason. The study shows that the posture of the modern politician and the crisis in society are the result of social changes caused by the metamorphoses of capitalism, but that politics itself presents possible solutions, based on collective and citizen participation.